"I'll Change His Sexual Orientation, I Don't Think About HIV": A Qualitative Study to Explore Attitudes, Behaviors, and Experiences Among Wives of Men Who Have Sex With Men in Mainland China. (July 2020) - Yan, Fang; Shi, Cynthia X.; Zhang, Ye; Chen, Jia; Williams, Ann Bartley; Li, Xianhong
Abstract : Supplemental Digital Content is Available in the Text. Abstract: In mainland China, HIV prevalence among men who have sex with men (MSM) has risen sharply in the past decade. However, few HIV studies have directly addressed the female spouses' ( tongqi ) experiences, a population estimated at 14 million [Cheng, F. K. (2016). I want to come forward: Voices from Chinese tongqi. Cogent Social Sciences, 2 (1), 1158343. doi:10.1080/23311886.2016.1158343; Zhu, J. (2018). "Unqueer" kinship? Critical reflections on "marriage fraud" in mainland China. Sexualities, 21 (7), 1075-1091. doi:10.1177/1363460717719240]. We conducted this exploratory qualitative study to understand tongqi's attitudes toward same-sex sexuality and HIV risk as well as their sexual history. Semistructured interviews were conducted with 24 tongqi between October 2015 and September 2016. Data were coded and analyzed using thematic analysis. We identified four primary themes: (a) surprise, initial disbelief, and negative attitudes toward their husbands' same-sex sexuality; (b) maintenance of regular sexual contact, particularly before pregnancy; (c) unprotected sex with marital and extramarital partners; and (d) low perception of HIV risk. Strategies to increase HIV knowledge and testing uptake are urgently needed among these vulnerable women but must be implemented with caution to avoid exacerbating high levels of homophobia.